Size at first maturity, oocyte envelopes and external morphology of the sperm in three species of Lucinidae (Mollusca: Bivalvia) from Florida Keys, USA - Bigatti, Gregorio (2004)
Gonads in the tropical lunicid bivalves Ctena orbiculata, Codakia orbicularis, and Lucina pensylvanica are located in the cephalopodial mass above the foot and behind the gills. Age estimates for Lucina pensylvanica suggest that individuals less than one year old are immature, as also is C. orbicularis, and that both males and females mature at two years. For Ctena orbiculata, we have no age data, but we consider that this species may also have early development. In July 2002 when water temperatures were high, mature individuals of all three species were spawning or in resorption, and oocyte envelopes were present. Parasites were found in the digestive diverticula of C. orbiculata and L. pensylvanica. External ultrastructure of the spermatozoon shows differences between the three species. Codakia orbicularis and L. pensylvanica have a long-headed spermatozoa, whereas Ctena orbiculata has a middle-size head. Codakia orbicularis possesses a flagellum with a lateral undulating membrane, absent from the two other species.